Benefit and safety of capecitabine after resection of biliary tract cancer: a real-world study with propensity score matching - Roussel, Hugo; Le Joncour, Sophie; Aurillac, Valerie; Marichez, Arthur; Blanc, Jean Frederic; Chiche, Laurence; Laurent, Christophe; Decraecker, Marie (Frontiers in Oncology, 2025)
Biliary tract cancer (BTC) is a high mortality disease, with few patients eligible for resection. Even post-surgery, recurrence rates remain high. The benefit of capecitabine as adjuvant therapy is uncertain, as seen in the BILCAP trial results. This study aimed to evaluate the impact of capecitabine in a real-world setting among patients who underwent surgery for localized BTC. This retrospective observational study compared a cohort of patients who received adjuvant capecitabine with an observation-only cohort. Recurrence-free survival (RFS) and overall survival (OS) were estimated and compared between the two groups, with propensity score matching to minimize selection bias. Differences in RFS were also analyzed between patients completing the full capecitabine protocol and those on an adapted protocol. From January 2017 to May 2023, 117 patients were included in the observation cohort, and 43 patients were included in the capecitabine cohort. After propensity score matching, no difference in RFS was found (HR = 0.700, P = 0.34). Additionally, RFS was similar between patients who completed the full capecitabine protocol and those who received an adapted protocol (HR = 0.265, P = 0.19). This study showed no clear benefit of capecitabine; further research is needed to improve survival outcomes.